Pelaksanaan Vaksinasi Covid 19 Dosis 2 - Aswin Wikantama; Happy Nurhayati; Rafika Noris (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The second dose of the COVID-19 vaccination plays a crucial role in enhancing protection against viral infection and strengthening the body's immune response. However, challenges remain in its implementation, including low public participation and limited awareness of the benefits of full vaccination. This study aims to evaluate the implementation of the second dose of COVID-19 vaccination, including participation rates, encountered barriers, and increased public awareness. The method used is a quantitative approach with a pre-test and post-test survey before and after vaccination education. The results indicate a significant increase in public understanding and participation after the educational intervention. Therefore, educational and socialization strategies should be continuously reinforced to optimize COVID-19 vaccination coverage.